Analisis Kinerja Keuangan Pt Ciputra Development Tbk (Ctra) Setelah Penerbitan Dana Investasi Real Estat (Dire) - Martin Teguh Wibowo (Universitas Tarumanagara, 2019)
Real Estate Investment Trust is known in Indonesian regulation as Dana Investasi Real Estat (DIRE). Many Indonesian listed developers are still not interested in DIRE as one of financing alternatives. This research aims to analyze the 2017 financial performance of PT Ciputra Development Tbk (CTRA) as a result of issuance of DIRE in terms of (i) funds received from DIRE issuance;(ii) dividend received from DIRE and (iii) its solvency ratios. The result of the research can be useful as (i) an input for management of CTRA that issuance of DIRE can be beneficial in terms of financial and (ii) a reference for investors for diversification in their investments. The method of this research is qualitative descriptive. The research used 2017 audited financial data for recurring income and its related expenses, fair value of recurring assets and some assumptions such as: 51% ownership of CTRA in DIRE, fees related to DIRE supporting institutions and issuance costs, as a basis for financial calculation of DIRE issuance. The result found that CTRA have (i) fresh fund from issuance of DIRE of Rp 3,7 trillion ; (ii) dividend from DIRE in 2017 of Rp 242 billion; and (iii) healthier solvency ratios after DIRE issuance i.e. lower DER and Debt ratio. The conclusion of this research is that CTRA have improved financial performance i.e. lowered solvency ratios and steady dividend streaming from DIRE every year. CTRA will have room for growth in the future to develop new projects.